The diagnostic value of routine antenatal ultrasound in screening for congenital uropathies. (17th January 2016) - de Grauw, Anne M.; den Dekker, Herman T.; de Mol, Amerik C.; Rombout-de Weerd, Sabina
Abstract: Background : Antenatal hydronephrosis (ANH) is characteristic for congenital obstructive abnormalities of the urinary tract (COAUT). COAUT is the most common cause of urinary tract infections (UTI's) in newborns. The prognosis of mild to moderate ANH is unclear. The aim of this study was to determine the diagnostic value of antenatal ultrasound screening for ANH in order to inform patients correctly. Methods : A retrospective cohort study over the period 2009–2011, evaluating all structural ultrasounds and proven cases of ANH. Also, evaluation of all patients diagnosed with UTIs caused by COAUT in the same period. Results : About 7003 children underwent antenatal screening. Of them, 0.7% ( n = 47) were diagnosed with ANH. In the same period, 257 children without ANH had a proven UTI. Of them, 4.3% ( n = 11) were diagnosed with COAUT, which was not found during antenatal screening. The predictive value of the antenatal ultrasound was higher in the third trimester than the second trimester (sensitivity 0.97 versus 0.62, respectively). Conclusion : Antenatal ultrasound screening is a reliable method in diagnosing ANH. Third trimester scanning is more specific for diagnosing ANH than second trimester scanning. Our findings allow collaborating gynecologists and pediatricians to inform patients more accurately in the future after the antenatal detection of COAUT.